Characterization of a natural fungicide from an indigenous plant Tasmannia piperita (Hook.f.) Miers extract stability, metabolomics, and in silico studies - Amaroso, Victor B.; Mendez, Rainear A.; Junio, Hiyas A.; Molino, Ralph John Emerson J.; Pescadero, Iris R.; Villalobos, Annabelle P. (Vol. 150, No. 2 (April 2021), pages 355-366.)
"Many indigenous plants are rich in secondary metabolites with fungicidal activity. Based on literature and focus group discussion (FGDs), seven species of indigenous plants as potential sources of fungicide were collected in several places in Mindanao Island and tested for phytochemicals. Among the seven species, Tasmannia piperita (Hook.f.) Miers showed the highest amount of phenolic and flavonoid content and was chosen for further studies "-title page.